Working out of built-in program code library for solving directional solidification crystal growth tasks - Konovalov, Vladimir Vladislavovich; Lyubimova, Tatyana Petrovna (Computational Continuum Mechanics, 2008)
Crystal Pack, a library with a built-in programming code, realized as a set of dll-libraries is presented. A key concept underlying the library is "certification" of computational domain points. Each domain point gets a "certificate" that explicitly identifies it among other points, and conveys the physical information retained at the digitization stage of the problem equations. It allows one to separate the setting part of the computational program from the program implementation of the numerical method, and to calculate the residuals of digitized equations of the problem solved in terms close to the formulation of the problem itself. The library has been tested for some simple problems, for example, its performance has been evaluated through investigating convection in a side-heated square cavity.